Biomimetic nanoparticles for effective mild temperature photothermal therapy and multimodal imaging - Shu, Xian; Chen, Yi; Yan, Ping; Xiang, Yun; Shi, Qun-Ying; Yin, Tinghui; Wang, Ping; Liu, Li-Han; Shuai, Xintao (Journal of controlled release, 2022)
Downregulation of adenosine triphosphate (ATP)-dependent heat shock proteins (HSPs) can significantly reduce the tumorigenicity of cancer cells and overcome heat endurance to achieve high-performance mild temperature (≤45 °C) photothermal therapy (PTT). Herein, we designed and constructed 4T1 cancer cell membrane-coated, lonidamine (LN)-loaded and DL-menthol (DLM)-loaded hollow mesoporous Prussian blue nanoparticles (PBLM@CCM NPs). DLM with mild phase change characteristics served as a plugging agent to avoid early leakage and allow thermally controllable release of LN, which enabled selective intracellular delivery of LN to reduce the HSPs and overcome the heat endurance in PTT by inhibiting the generation of intracellular ATP. The biocompatible PBLM@CCM NPs with good tumor targeting efficiency achieved high-efficiency mild temperature PTT. Meanwhile, PBLM@CCM NPs could allow photoacoustic (PA) imaging and generate heat to promote the phase change of DLM for ultrasound (US) imaging, which is of great value for future clinical translational studies. [Display omitted] •Nanodrug was coated with 4T1 cell membrane for tumor-targeting drug codelivery.•NIR light irradiation-triggered LN release decreased HSPs expression to enhance PTT.•PA/US/Photothermal multimodal imaging abilities were demonstrated.